Occupational Asthma and Work-Exacerbated Asthma - Friedman-Jimenez, George; Harrison, Denise; Luo, Honghong (Seminars in Respiratory and Critical Care Medicine, 2015)
Occupational asthma (OA) and work-exacerbated asthma (WEA), collectively known as work-related asthma (WRA), have been recognized as the most prevalent work-related lung diseases in the industrialized world. OA is asthma caused by workplace conditions, and is subdivided into sensitizer-induced (allergic) OA and irritant-induced (nonallergic) OA. WEA is asthma that is made worse, but was not initially caused, by workplace conditions. Although WRA is rarely fatal, patients with WRA frequently experience excessive time lost from work, workplace-specific severe disability, loss of income, job loss, and related psychosocial and financial problems. More than 400 workplace environmental agents have been reported to cause WRA, and are classified by molecular weight and allergenic and irritant properties. Diagnosis of WRA requires confirmation of a diagnosis of asthma plus evidence that the asthma was caused or worsened by workplace conditions. Accuracy of diagnosis is important because either overdiagnosis or missed diagnosis of WRA can be problematic for the patient. Self-reported clinical symptoms alone have only fair sensitivity and specificity for OA. If possible, diagnostic assessment should also include objective evidence with functional and immunologic testing. Treatment and prevention of onset or worsening of WRA can be highly effective and typically include both optimal medical management (generally the same as for non-WRA) and, importantly, avoidance of sensitizer or irritant exposures that caused or exacerbate the asthma. In most cases of OA, prognosis is better with cessation rather than reduction of exposure, and this may require substantial changes in the workplace environment or change of job or even profession.
Keywords: occupational asthma; work-exacerbated asthma; work-related asthma; irritant-induced asthma; peak expiratory flow; nonspecific bronchial hyperresponsiveness; diagnosis; sensitivity; specificity; prevention